Antibiotic Resistance among Klebsiella pneumoniae Isolates by Detecting blaVIM and blaNDM Genes - Narjes Mohammadi Bandari (Journal of Medical Microbiology and Infectious Diseases, 2020)
Introduction: The emergence of extended-spectrum β-lactamase (ESBL) and carbapenem-resistant Enterobacteriaceae, especially Klebsiella pneumoniae isolates, has become a severe concern worldwide. This study aimed to determine the prevalence of blaVIM and blaNDM genes among K. pneumoniae isolates.  Methods: One hundred-eighty-one K. pneumoniae isolates were obtained from different clinical specimens of patients hospitalized at Firoozgar hospital, Tehran, Iran. The isolates were identified by standard biochemical tests, and their identity was confirmed by Vitek 2 (bioMérieux, France), a fully automated system for bacterial identification. The isolates were subjected to antimicrobial susceptibility testing and screened for ESBL by double-disc synergy test (DDST) and modified Hodge test (MHT) for the detection of carbapenemase. PCR was also used to detect the presence of blaVIM and blaNDM resistance genes in the isolates. Results: The Vitek 2 system confirmed the biochemical test results. The highest and lowest rates of resistance to antibiotics belonged to cefepime (83.9%) and imipenem (55.2%).  Eighty-six and 100 isolates showed to produce ESB and KPC by DDST and MHT, respectively. About 71% and 97% of the 100 isolates were positive for blaVIM and blaNDM genes, respectively. Conclusion: The high rate of ESBL- and KPC-producing K. pneumoniae isolates in our hospital setting revealed resistance to conventional antibiotics, which limit our options in choosing appropriate antimicrobials. Although the management of infections associated with these organisms is challenging, it is essential to control such strains to prevent the outbreak.